STUDI KOMPARASI HASIL BELAJAR ANTARA PENERAPAN METODE SEMINAR DAN METODE TUGAS PERSIAPAN DALAM PEMBELAJARAN SEJARAH - Anwar, Khoirul (Indonesian Journal of History Education, 2012)
This is a comparative study of two methods of learning the experimental method and the method of assignment preparation seminar. The purpose of this study was to determine the learning outcomes of students who were taught by both methods, as well as knowing the difference between the methods of implementation of tasks and methods of preparation seminar. The approach of this research is to experimentally study the entire population of students class XI IPS 3 Demak SMA, while the sample taken is class 1 and class XI IPS XI IPS 3. Study results indicate that a class of students who were taught using seminars obtained better results than the class taught by the method of preparation tasks, although both performed equally well. Suggestions presented in this study is that Learners need to be encouraged to be active participants in learning; and seminar methods and preparation task method can be applied in teaching history to make students active in learning.